Optimal adjustment paths in a monetary union - Belke, Ansgar; Gros, Daniel (Brussels, 2016)
"Adjustment to an external imbalance is more difficult within a monetary union if wages are sticky. Periods of high unemployment are usually necessary to achieve the required real depreciation (internal devaluation). Gradual adjustment is usually recommended to distribute the output and employment cost over time. This paper takes into account that gradual adjustment also has a cost in terms of higher current account deficits and thus a higher debt, and ultimately higher debt-service costs. We calculate the optimal path/speed of price and wage adjustment in terms of deeper parameters like the slope of the Phillips curve, the degree of openness, etc. Gradual adjustment is not always optimal."